MONNAIE NUMERIQUE DE BANQUE CENTRALE (ou Central Bank Digital Currency) – REVUE DE LITTERATURE - Tina Michel RAKOTOARISOA (Modern Scientific Technology, 2025)
The growing interest in Central Bank Digital Currencies (CBDCs) reflects profound structural transformations in the global monetary system, including accelerating payment digitization, the rise of private cryptocurrencies, and central banks’ efforts to preserve monetary sovereignty. This paper provides a systematic review of both institutional and academic literature on CBDCs, drawing on major contributions from international organizations and central banks, as well as peer-reviewed economic research. The analysis highlights how institutional frameworks emphasize CBDCs as instruments for modernizing monetary systems, enhancing financial inclusion, and improving cross-border payments, while academic studies focus on their macroeconomic implications, particularly for financial stability, banking intermediation, and monetary policy transmission. The review reveals a fragmented research landscape, characterized by ongoing debates over the trade-offs between innovation and stability, as well as between centralization and competition in digital currency design. Importantly, the paper underscores the lack of robust ex post empirical evidence on the long-term effects of CBDCs on deposits, credit markets, financial stability, and policy effectiveness. It further stresses the importance of international coordination to mitigate the risk of monetary and financial fragmentation. Overall, the paper contributes to the literature by synthesizing existing findings and identifying key research gaps, with particular attention to the potential role of CBDCs in supporting financial inclusion and economic development in emerging economies.